THE CORRELATION AMONG MOTIVATION, WAYS OF LEARNING, AND WAYS OF TEACHING TOWARD ENGLISH ACHIEVEMENT AMONG THE FIRST YEAR STUDENTS OF SMAN 1 GROGOL - Ramiasih, Yanti (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of this research is to know whether there is any significant correlation among motivation, ways of learning and ways of teaching toward English achievement among the first year students of SMAN 1 Grogol.  The design used descriptive quantitative correlation research design.it was conducted in SMAN 1 grogol. The population was 306 of the first year students o SMAN 1 Grogol. while, the sample of this research was 170 students. The instrument was used in this research were questionnaire, test and documentation. The data gotten was analyzed by SPSS version 11.00 to find descriptive, simultaness and partial correlation. The result of the resarch are: Motivation belong to â€œenoughâ€œ while the precentage is 69,4%, the studentsâ€™ ways of learning belong to â€œgoodâ€ while the precentage is 48,2%, studentsâ€™ ways of teaching belong to â€œgoodâ€ while the precentage is 60,6%, and English achievement belong to â€œmoderateâ€ category while the precentage is 35,9%. Simultaneously, motivation, the ways of learning, and ways of teaching  has influenced 2.9% to the English achievement, so can be said â€œvery lowâ€ correlation. Than Partially, correlation of English achievement and learning facilities, the ways of learning and motivation were  0.028, -0.107, 0.042 can be said â€œvery lowâ€ correlation